2015
DOI: 10.1371/journal.pone.0138566
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin Identifies Cell Injury, Not Bacterial Infection, in Acute Liver Failure

Abstract: BackgroundBecause acute liver failure (ALF) patients share many clinical features with severe sepsis and septic shock, identifying bacterial infection clinically in ALF patients is challenging. Procalcitonin (PCT) has proven to be a useful marker in detecting bacterial infection. We sought to determine whether PCT discriminated between presence and absence of infection in patients with ALF.MethodRetrospective analysis of data and samples of 115 ALF patients from the United States Acute Liver Failure Study Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 31 publications
1
36
0
4
Order By: Relevance
“…A limited number of paired PCT and other laboratory marker measurements could be assessed for correlation (Table 5). PCT correlated with liver function test measurements (most strongly with γ-glutamyl transpeptidase), indicating that PCT in DRESS may be an indicator of hepatic tissue damage as found by other investigators [73]. There was no correlation between PCT and eosinophil count (21 paired observations), suggesting that the pathomechanisms of PCT elevation and eosinophilia in DRESS syndrome are independent of each other.…”
Section: Crp Pct Leukocyte and Eosinophil Valuessupporting
confidence: 59%
See 1 more Smart Citation
“…A limited number of paired PCT and other laboratory marker measurements could be assessed for correlation (Table 5). PCT correlated with liver function test measurements (most strongly with γ-glutamyl transpeptidase), indicating that PCT in DRESS may be an indicator of hepatic tissue damage as found by other investigators [73]. There was no correlation between PCT and eosinophil count (21 paired observations), suggesting that the pathomechanisms of PCT elevation and eosinophilia in DRESS syndrome are independent of each other.…”
Section: Crp Pct Leukocyte and Eosinophil Valuessupporting
confidence: 59%
“…Indeed, PCT elevation has been observed in cases of liver injury independent of the presence of bacterial infection. Rule et al [73] found a median PCT value of > 1.57 ng/mL in 59 patients with acute liver failure without sepsis. There was also no significant difference in PCT values between the 56 patients with and the 59 patients without bacterial infection.…”
Section: Crp Pct Leukocyte and Eosinophil Valuesmentioning
confidence: 98%
“…[24] A recent study looking at PCT concentrations in acute liver failure patients also found poor correlation between sepsis and PCT levels in this type of patients, presumably due to presence of extensive inflammation. [25] Regardless, our study attempted to study all ICU patients rather than a specific cohort.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In our study, hepatic macrophages but not hepatocytes were found to be the cell source of hepatic PCT upregulation in ALF. Moreover, previous studies have shown that serum PCT is elevated in patients with ALF and ACLF [10,27,28], and the liver is one of the main sources of elevated serum PCT [7,29,30] in sepsis and cytokine storms. Thus, further study is required to clarify the involvement of hepatic PCT-especially that expressed by hepatic macrophages-in the elevation of serum PCT.…”
Section: Discussionmentioning
confidence: 99%